Vitamin C supplementation promotes locomotor and exploratory behaviors in male Wistar rats exposed to varying stress models (Nigerian Journal of Physiological Sciences, 2023)
Constant exposure to environmental stress has negative behavioral outcomes. Considering the inverse relationship between stress and Vitamin C intake, this study was aimed at investigating variable stress techniques and Vitamin C supplementation on exploratory/locomotor behaviors in male Wistar rats. Twenty-eight male Sprague-Dawley rats (100g-120g) were allotted into four groups (n=7). Control received 10ml/kg distilled water, group two received 100 mg/kg vitamin C, group three was exposed to different models of stress while group four was stressed alongside 100 mg/kg vitamin C. Vitamin C treatments were given orally for 2 weeks. Animals in groups 3 and 4 were stressed every other day with models such as multiple cage changes, exposure to noise, overnight strange objects, overnight wetting of beddings, and immobility. Explorative and locomotor activities were assessed with the open field test, novel object recognition test, and Y maze test using a Logitech camera and ANY-maze software to track the movement of the rats. Cortisol was assayed in the serum using Enzyme-linked Immuno Assay (ELISA) kit. Superoxide Dismutase, catalase, and lipid peroxidase; malondialdehyde (MDA) were also assayed in the serum. The results show that locomotor activities such as distance traveled, average speed, and time spent in the center square was significantly reduced by stress. These activities were improved with the intake of vitamin C compared with stress. Explorative activities such as locomoting around the environment, orientating towards novelty, and touching or sniffing novel objects were significantly increased in the rats on Vitamin C supplements and reduced in the stressed group. In the serum, cortisol level was significantly increased in rats exposed to stress and decreased with Vitamin C intake. Stress also significantly increased MDA and decreased SOD and CAT while vitamin C supplement decreased MDA and increased SOD and CAT. In conclusion, oral intake of vitamin C enhanced explorative/locomotor behavior and increased oxidative stress in rats exposed to different models of stress